2007
DOI: 10.1377/hlthaff.26.3.841
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice Liability Costs And The Practice Of Medicine In The Medicare Program

Abstract: This analysis suggests that an important association exists between malpractice costs and the use of imaging services in particular.by Katherine Baicker, Elliott S. Fisher, and Amitabh Chandra ABSTRACT: Mounting malpractice liability costs might affect physician practice patterns in many ways, such as increasing the use of diagnostic procedures while reducing major surgeries. This paper quantifies the association between malpractice liability costs and the use of physician services in Medicare. We find that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 20 publications
11
123
1
Order By: Relevance
“…This conclusion is similar to those of other recent studies, 18,21,23 and to that of the Congressional Budget Office (CBO). 24 There is a caution that applies to our cost estimate, as well as those of all empirical analyses of defensive medicine, including the CBO study referred to above.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This conclusion is similar to those of other recent studies, 18,21,23 and to that of the Congressional Budget Office (CBO). 24 There is a caution that applies to our cost estimate, as well as those of all empirical analyses of defensive medicine, including the CBO study referred to above.…”
Section: Resultssupporting
confidence: 92%
“…[18][19][20] Other studies have found weak relationships, or no relationships at all, between either malpractice premiums and health care costs or direct reforms and health care costs. 16,17,21,22 Nearly all of the studies cited above focused on limited sets of clinical conditions or clinical specialties, or both. However, a few recent studies have used data supporting more comprehensive estimates of defensive medicine costs, and these suggest that reforms aimed at limiting damage awards are likely to lead to only modest cost savings.…”
Section: -17mentioning
confidence: 99%
See 1 more Smart Citation
“…Defensive medicine due to perceived medicolegal liability is widespread 17,45 and has been linked with higher imaging use and health care costs. 16,17,[45][46][47][48] While some have advocated that tort reform should be central to policies aimed at reducing excessive medical spending, 45,49 studies evaluating the effect of actual reform efforts have demonstrated a limited effect on cost reduction and physician behavior. 46,[49][50][51][52][53][54] However, given the high malpractice concern among physicians in our sample and others, 17,45,51 we believe that although tort reform would not be sufficient to eliminate overuse, 54 it may be a necessary initial step.…”
Section: Discussionmentioning
confidence: 99%
“…Claims expenditures of German liability insurance companies have doubled to 120 million euros between 2000 and 2009. A positive correlation between increasing patient compensation and health care expenditures was demonstrated by Baicker et al [1]. US federal states assigning high malpractice liability, registered increasing health care costs by 7% and a per-physician raise in expenditures of 4.2%.…”
mentioning
confidence: 87%